(untitled) (Baghdad Science Journal, 2021)
The Atmospheric Infrared Sounder (AIRS) on EOS/Aqua satellite provides diverse measurements of Methane (CH4) distribution at different pressure levels in the Earth’s atmosphere. The focus of this research is to analyze the vertical variations of (CH4) volume mixing ratio (VMR) time-series data at four Standard pressure levels SPL (925, 850, 600, and 300 hPa) in the troposphere above six cities in Iraq from January 2003 to September 2016. The analysis results of monthly average CH4VMR time-series data show a significant increase between 2003 and 2016, especially from 2009 to 2016; the minimum values of CH4 were in 2003 while the maximum values were in 2016. The vertical distribution of CH4 was relatively high in the cities located in the north of Iraq (Sulaymaniyah and Mosul) more than other cities, especially these in western Iraq (Rutba and Najaf). The highest monthly mean of CH4VMR and standard deviation (SD) was in Sulaymaniyah (1871.11±21.92) ppbv at 925 hPa, while the lowest was in Rutba (1812.81±37.3) ppbv at 300 hPa. Mosul has the second-highest mean and SD next to Sulaymaniyah, especially at the lower levels SPL (925 and 850 hPa) of troposphere more than the rest of selected cities. The seasonal variation of monthly CH4VMR, averaged from 2003 to 2016, shows high values between January and August with a peak between August and September and it declines significantly between October and December with a slight increase in November. Long term trend analysis of monthly CH4VMR at each SPL (925, 850, 600, and 300) hPa above the six cities shows positive values with average growth rates for each SPL equal to (2.9 %, 3.1%, 3.6 %, and 3.9%), respectively. These results indicate that satellite measurements were effective in determining the magnitude of increased CH4 over Iraq that may contribute to the global increase of CH4 in the earth’s Atmosphere.